2023
DOI: 10.1186/s12912-023-01258-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to a successful professional development for specialist nurses in surgical care: a cross-sectional study

Abstract: Background A high level of competence among staff is necessary for providing patient-safe surgical care. Knowledge regarding what factors contribute to the professional development of specialist nurses in surgical care and why they choose to remain in the workplace despite high work requirements is needed. To investigate and describe the organizational and social work environment of specialist nurses in surgical care as part of studying factors that impact on professional development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
2
4
0
4
Order By: Relevance
“…A positive working atmosphere, with harmonious interpersonal relationships and mutual trust among members, enhances team cohesion and contributes to team development. In line with the findings of Drott et al [ 58 ], we found that the interactive relationships between leaders and their subordinates as well as employees’ supportive aspects can affect individuals’ development. A qualified leader can think differently and provide help and guidance to subordinates, thus motivating and driving the entire nursing team in the department [ 59 ].…”
Section: Discussionsupporting
confidence: 92%
“…A positive working atmosphere, with harmonious interpersonal relationships and mutual trust among members, enhances team cohesion and contributes to team development. In line with the findings of Drott et al [ 58 ], we found that the interactive relationships between leaders and their subordinates as well as employees’ supportive aspects can affect individuals’ development. A qualified leader can think differently and provide help and guidance to subordinates, thus motivating and driving the entire nursing team in the department [ 59 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moving into the sphere of “Documentation and Administration of Nursing Care”, nurses in our study had a very good competency level in developing a collaborative care plan and documentation skills echoing the significance of nursing documentation and administration for ensuring high-quality patient care [ 36 ], Additionally, the participant’s had very good competency in “Development, Leadership, and Organization of Nursing Care” which underscored the nursing abilities to lead and supervise teamwork and prioritize care aligning with the findings of various studies supporting this notion [ 37 39 ].…”
Section: Discussionsupporting
confidence: 66%
“…Os serviços cirúrgicos contam com uma equipa de saúde especializada que cuida de clientes durante o seu internamento. Esta equipa inclui enfermeiros, médicos, fisioterapeutas, nutricionistas e outros profissionais de saúde que trabalham em conjunto para prestar cuidados integrais e individualizados (Drott et al, 2023;GurKová et al, 2021;Mamatkulov et al, 2022). A equipa de saúde presta cuidados pré e pós-operatórios centrados no controle dos sintomas e na recuperação física do processo cirúrgico, mas também nas recomendações e instruções ao cliente e sua família sobre os cuidados para a alta (Drott et al, 2023;Mamatkulov et al, 2022).…”
Section: Introductionunclassified
“…Aljezawi (2020) no seu estudo, destaca a importância do apoio social no processo de integração de novos enfermeiros. Para a autora, o apoio social auxilia os novos enfermeiros na adaptação ao ambiente de trabalho e à cultura organizacional (Drott et al, 2023;GurKová et al, 2021;Mamatkulov et al, 2022). Por outro lado, uma boa integração auxilia na retenção dos enfermeiros, reduz a rotatividade e favorece sentimentos de valorização pelo seu trabalho (Drott et al, 2023;GurKová et al, 2021;Kaveh et al, 2020;Ma et al, 2018;Mamatkulov et al, 2022).…”
Section: Introductionunclassified
See 1 more Smart Citation